Time Trends and Predictors of Acute Gastroenteritis in the United States: Results From National Health and Nutrition Examination Survey 2005-2014. Issue 8 (September 2017) - Kim, Hyun S.; Rotundo, Laura; Nasereddin, Thayer; Ike, Adaugo; Song, David; Babar, Arooj; Feurdean, Mirela; Demyen, Michael F.; Ahlawat, Sushil K.
Abstract : Goals: To investigate the time trends of the prevalence and predictors of acute gastroenteritis (AGE) in the United States from 2005 to 2014 using nationally representative data. Background: AGE results in numerous visits to emergency departments and outpatient clinics annually in the United States with the estimated attributable cost to the US economy up to 145 billion dollars. However, time trends and predictors of AGE are not fully understood. Methods: Data were obtained from the National Health and Nutrition Survey (NHANES) 2005 to 2014, a nationally representative health survey. AGE was defined by a medical question (Do you have a stomach or intestinal illness with vomiting or diarrhea that started during last 30 d?). Prevalence of AGE was estimated in the total population as well as by selected demographic variables. Predictors of AGE and time trends of prevalence over survey periods were also investigated. Results: Overall monthly prevalence of AGE was 8.31% (95% confidence interval, 7.81-8.81), corresponding to 22.8 million people. AGE was associated with a younger age group, the highest in ages 0 to 9 years old, females, winter to early spring season, US born, divorced/separated/widowed individuals, current smokers, heavy alcohol users, and low household income. In the trends analyses, the prevalence of AGE significantly decreased over the study periods: 10.23% in 2005 to 2006, 9.89% in 2007 to 2008, 7.58% in 2009 to 2010, 6.44% in 2011 to 2012, and 7.47% in 2013 to 2014 (trend P <0.001). Conclusion: In the United States from 2005 to 2014, the monthly prevalence of AGE was 8.31% and has been significantly decreasing over time.